The middle-income trap: Issues for members of the Association of Southeast Asian Nations - Tran Van Tho (Asian Development Bank Institute (ADBI), 2013)
The problem faced by many of the economies making up the Association of Southeast Asian Nations (ASEAN) is whether they can avoid the middle-income trap and advance to the high-income level. What is needed for them to avoid the middle-income trap? This paper attempts to answer this question by building an analytical framework based on the factors that determine each development stage of an economy, and by comparing the current situation of four ASEAN middle-income countries with the experience of the Republic of Korea, a country that managed to overcome the middle-income trap and reach the high-income level in the late 1990s. The paper concludes that for ASEAN middle-income countries (Indonesia, Malaysia, the Philippines, and Thailand) to avoid the trap, they should strengthen research and development capability, emphasize the quality and appropriateness of human resources, and improve the institutional system for nourishing a dynamic private sector. These efforts can be expected to result in dynamic changes in the structure of comparative advantage toward higher skill and more innovation-intensive contents of products. For a low middle-income country such as Viet Nam, reforms and policies to increase the productivity of capital, land, and other resources are essential to avoid the early appearance of the trap.
Keywords: O10; O11; O40; O43; O53; 330; asean; middle-income trap; republic of korea; viet nam; indonesia; malaysia; philippines; thailand; Wirtschaftswachstum; Bruttoinlandsprodukt; Nationaleinkommen; Entwicklungskonvergenz; Wirtschaftliche Anpassung; Indonesien; Malaysia; Philippinen; Thailand; Südkorea